2020
DOI: 10.1007/s11224-020-01605-w
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing metocurine as main protease inhibitor to develop novel antiviral therapy for COVID-19

Abstract: The outbreak of severe acute respiratory syndrome coronavirus-2 is causing a serious disaster through coronavirus disease-19 (COVID-19) around the globe. A large segment of the population from every corner of the world is already infected with this dreadful pathogen with a high mortality rate. These numbers are increasing drastically causing a situation of a global pandemic. Although after the continuous scientific efforts, we are still not having any specific drug or vaccine for the SARS-CoV-2 pathogen to dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 14 publications
0
59
0
Order By: Relevance
“…The M pro (nsp5), encoded by the major ORF1ab, cleaves two overlapping polyproteins (pp1a and pp1ab) into 16 non-structural proteins which are important for viral replication and maturation ( Paul, 2006 ; Ziebuhr et al, 2000 ; Chen et al, 2020b ; Gordon et al, 2020 ). In addition, it plays a significant role in virus entry to host cells where inhibition of this enzyme halts the viral entry and the subsequent infection ( Jain and Mujwar, 2020 ). These important functions of the viral protease enzyme purpose itself are an interesting therapeutic target for curbing coronavirus associated diseases ( Thiel et al, 2003 ; Naqvi et al, 2020 ).…”
Section: Sars-cov-2 M Pro As a Drug Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…The M pro (nsp5), encoded by the major ORF1ab, cleaves two overlapping polyproteins (pp1a and pp1ab) into 16 non-structural proteins which are important for viral replication and maturation ( Paul, 2006 ; Ziebuhr et al, 2000 ; Chen et al, 2020b ; Gordon et al, 2020 ). In addition, it plays a significant role in virus entry to host cells where inhibition of this enzyme halts the viral entry and the subsequent infection ( Jain and Mujwar, 2020 ). These important functions of the viral protease enzyme purpose itself are an interesting therapeutic target for curbing coronavirus associated diseases ( Thiel et al, 2003 ; Naqvi et al, 2020 ).…”
Section: Sars-cov-2 M Pro As a Drug Targetmentioning
confidence: 99%
“…His 163 and Glu 166 side chains form a hydrogen bond with the glutamine surrogate in the P1 position whereas a hydrophobic interaction was noticed with His 172 while hydrogen bond connects the backbone amide of Glu 166 with carbonyl in the P3, suggesting the strong binding capacity of the drugs on the catalytic site of the M pro . A simulation study by Jain and Mujwar, (2020) showed that Metocurine, a neuromuscular blocking agent, binds specifically with the substrate-binding cavity of the protease enzyme supported with residues Phe 140 , Leu 141 , Cys 145 , His 163 , His 164 , Met 165 , Glu 166 , Leu 167 , and Pro 168 repurposing the compound as a safe and effective prospective drug.…”
Section: Structure-based Design Of Drugs That Target Sars-cov-2 M Promentioning
confidence: 99%
“…The π-stacking interaction between His41 and EbSe is in agreement with the data by Cozza. [23] In addition, the hydrophobic interaction with Met49, His41, and Met165 residues, [75][76][77] and H-bonds with Ser144 [78,79] plays an important role in the inhibitor-enzyme complex stabilization in SARS-CoV-2 Mpro.…”
Section: Ebse Interactions With Mpro Active Sitementioning
confidence: 99%
“…Specifically, most studies on drugs targeting the main protease of SARS-CoV-2 present only data related to the in vitro potency and safety while in vivo pharmacokinetic profiling is very limited. The main protease is a crucial enzyme for virus replication and maturation ( Ziebuhr et al, 2000 ; Jain and Mujwar, 2020 ) and has a relatively conserved active site ( Stoermer, 2020 ; Ullrich and Nitsche, 2020 ) which makes it considered as a potential drug target ( Naqvi et al, 2020 ). Remarkably, there are promising baseline data on potential inhibitors of SARS-CoV-2 M pro .…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Promising drugs targeting SARS-CoV-2 M pro have been under investigation demonstrating efficient binding and potential antiviral activities. The main protease is a key enzyme important for viral replication and maturation ( Ziebuhr et al, 2000 ; Jain and Mujwar, 2020 ). Besides, the M pro has enhanced enzymatic activity and there are no human proteases reported yet having similar specificity with it ( Hilgenfeld, 2014 ; Zhang et al, 2020a , Zhang et al, 2020b , Zhang et al, 2020c ) strengthening its preference of being a potential drug target.…”
Section: Introductionmentioning
confidence: 99%